2001
DOI: 10.1079/pns2001110
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines and adipose tissue

Abstract: Cytokines appear to be major regulators of adipose tissue metabolism. Therapeutic modulation of cytokine systems offers the possibility of major changes in adipose tissue behaviour. Cytokines within adipose tissue originate from adipocyte, preadipocyte and other cell types. mRNA expression studies show that adipocytes can synthesise both tumour necrosis factor a (TNF-a) and several interleukins (IL), notably IL-1b and IL-6. Other adipocyte products with ‘immunological’ actions include complement system product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
579
2
55

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 880 publications
(649 citation statements)
references
References 88 publications
(118 reference statements)
13
579
2
55
Order By: Relevance
“…White adipose tissue plays a central role in the low grade inflammatory state that is characteristic of obesity [25,26]. In fact, adipose tissue is a potent source of inflammatory interleukins and other circulating cytokines, the secretion of which increase with adiposity [25][26][27]. In agreement with previous studies [20,28], we have found a significant correlation between basal hs-CRP and BMI.…”
Section: Discussionsupporting
confidence: 91%
“…White adipose tissue plays a central role in the low grade inflammatory state that is characteristic of obesity [25,26]. In fact, adipose tissue is a potent source of inflammatory interleukins and other circulating cytokines, the secretion of which increase with adiposity [25][26][27]. In agreement with previous studies [20,28], we have found a significant correlation between basal hs-CRP and BMI.…”
Section: Discussionsupporting
confidence: 91%
“…In this study we could not find any independent associations between plasma levels of TNF-α or IL-6 and fat cell size or insulin resistance. As suggested previously, these adipokines may have mainly paracrine effects [14,37].…”
Section: Discussionmentioning
confidence: 62%
“…It has been suggested that the increased oxidant stress that is associated with obesity may be due to the presence of excessive adiposity per se because adipocytes and preadipocytes have been identified as sources of inflammatory cytokines, including TNF-α, interleukin (IL)-1-β and IL-6 [34]. Cytokines are potent stimuli for the production of ROS/RNS by macrophages and monocytes [35]; therefore, we examined the effect of chronic UVB exposure on the secretion of pro-inflammatory cytokines.…”
Section: Uvb Exposure-induces Higher Levels Of Secretion Of Pro-inflamentioning
confidence: 99%